2019
DOI: 10.1182/blood-2019-122971
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation and Treatment (Tx) of Burkitt Lymphoma (BL) in the Modern Era: Real World (RW) Outcomes and Prognostication across 26 US Cancer Centers (CC)

Abstract: Introduction: Historically, outcomes for BL have improved in adults using dose intensive chemotherapy regimens and early CNS prophylaxis. More recent data using a less intensive regimen, DA-EPOCH, have been reported. We analyzed detailed patient (pt) & disease characteristics and treatment patterns across 26 US CCs over a recent 9 year (yr) period and also determined survival rates & prognostication. Methods: We conducted a large multicenter retrospective study of newly diagnosed (dx) ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 0 publications
3
23
0
Order By: Relevance
“…Subsequently, a recent phase 2 study of risk-adapted DA-EPOCH-R adopted this classification system for patient stratification and allocation to different chemotherapeutic intensities [13]. Although each factor comprising this risk-stratifying criterion was shown to be prognostic in patients with BL [6][7][8][9][10], to our knowledge, the validity of the previously suggested system has not been thoroughly confirmed as a robust prognostic index for BL patients. Since the chemotherapy regimens were not significantly different between the different risk groups based on the previously suggested criteria, no definite difference in our study in the survival outcomes of patient subgroups based on these criteria indicates that they have room for improvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, a recent phase 2 study of risk-adapted DA-EPOCH-R adopted this classification system for patient stratification and allocation to different chemotherapeutic intensities [13]. Although each factor comprising this risk-stratifying criterion was shown to be prognostic in patients with BL [6][7][8][9][10], to our knowledge, the validity of the previously suggested system has not been thoroughly confirmed as a robust prognostic index for BL patients. Since the chemotherapy regimens were not significantly different between the different risk groups based on the previously suggested criteria, no definite difference in our study in the survival outcomes of patient subgroups based on these criteria indicates that they have room for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the highly aggressive biological behavior of BL, the patterns of disease involvement and clinical course show substantial heterogeneity [1][2][3][4]. Population-based studies have identified several risk factors for a poor outcome among patients with BL, such as older age, advanced stage, African ancestry, poor performance status (PS), and high levels of lactate dehydrogenase (LDH) [5][6][7][8][9][10]. A recent multicenter study reported age, Eastern Cooperative Oncology Group (ECOG) PS, LDH, and central nervous system involvement as independent prognostic factors for the survival outcomes of patients with BL [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-risk patients could be treated with intensified R-CODox-M/IVAC or R-Hyper-C-VAD/MA, as these regimens are indicated for patients with CNS involvement and associated with a significantly reduced risk of CNS relapse in comparison to DA-R-EPOCH in patients with no CNS involvement at diagnosis. [ 95 96 97 ] For patients treated with DA-R-EPOCH, the second cycle and beyond can be administered in an outpatient ambulatory setting, if hospital resources are available. [ 98 ] On the other hand, for patients with low-risk disease, three cycles of DA-R-EPOCH is adequate treatment and associated with excellent outcome.…”
Section: Aggressive B-cell Lymphomasmentioning
confidence: 99%
“…However, there is no standardized prognostic model for adult BL. Recently, in a multicenter real-world study in Western countries presented that ages ≥ 40, Eastern Cooperative Oncology Group (ECOG) performance status (PS) ≥ 2, LDH 3 times more than the upper normal limit and central nervous system (CNS) involvement predicted inferior survival and constructed a BL-IPI in adult BL (13,14). But the prognostic model for adult patients with sporadic BL in Asian patient is still under establishment.…”
Section: Introductionmentioning
confidence: 99%